Lesson from nature: Zataria multiflora nanostructured lipid carrier topical gel formulation against Candida-associated onychomycosis, a randomized double-blind placebo-controlled clinical trial - Maryam Moazeni; Hamidreza Kelidari; Yaser Nasirzadehfard; Tahereh Shokohi; Behrad Roohi; Zohreh Hajheidari; Armaghan Kazeminejad; Shima Parsay; Kofi Asare-Addo; Ali Nokhodchi (Elsevier, 2024)
Purpose: The increasing resistance to onychomycosis treatment globally is a major concern as it results in treatment failures. This research aimed to investigate the effectiveness of incorporating nanostructured lipid carriers (NLCs) in a gel formulation for treating mild to moderate Candida-associated onychomycosis using Zataria multiflora (Zt) essential oils. Methods: The characteristics of Zataria multiflora-loaded nanostructured lipid carriers (Zt-NLCs) were validated using a carbopol gel (1 % w/w). In vitro tests were conducted using CLSI M60 standards to evaluate the susceptibility of ten commonly encountered dermatophyte species to antifungal agents. A clinical study was conducted involving 40 volunteers randomly assigned to two groups: one receiving the Zt-NLCs gel and the other receiving a placebo, using a double-blind, placebo-controlled design. The objective was to assess clinical manifestations and mycological findings after topical application for 2 and 4 weeks. The causative agents' species were identified using a PCR-RFLP method. Results: The preparation of Zt-NLCs gel resulted in a uniform suspension of spherical nanoparticles with favourable characteristics and no cytotoxic effects. Zt-NLCs demonstrated significant inhibitory effects on fungal growth and effectively improved clinical and mycological criteria in comparison to the placebo group (p < 0.005), even after 2 weeks of treatment. The C. albicans complex was recognized as the predominant species isolated from the patients using PCR-RFLP. Conclusion: The administration of Zt-NLCs gel for two weeks showed significant efficacy in disease management, as reported by both dermatologists and mycologists and therefore shows its potential use as a treatment against Candidal onychomycosis.